Agreement Between Peak Inspiratory Pressure in Decelerating-Flow Ventilation and Plateau Pressure in Square-Flow Ventilation in Pediatric Acute Respiratory Distress Syndrome*. Issue 3 (March 2022) - Patel, Bhavesh; Thomas, Neal J.; Yehya, Nadir
Abstract : OBJECTIVES: Acute respiratory distress syndrome guidelines suggest limiting plateau pressures to 28–30 cm H2 O. Plateau pressure is most accurately measured in square-flow modes, such as volume control. In children, decelerating-flow modes, such as pressure-regulated volume control and pressure control, are more common. Consequently, plateau pressures are rarely obtained, and pressure limits are instead provided for peak inspiratory pressure. The degree to which peak inspiratory pressure in decelerating-flow overestimates plateau pressure is unknown. Therefore, we assessed the correlation and accuracy of peak inspiratory pressure in decelerating-flow ventilation for approximating plateau pressure during square-flow ventilation. DESIGN: Prospective, observational study. SETTING: Tertiary, academic PICU. PATIENTS: Fifty-two intubated children with acute respiratory distress syndrome enrolled between January 2020 and May 2021. INTERVENTIONS: Measurement of peak inspiratory pressure in decelerating-flow ventilation and plateau pressure after transition to square-flow ventilation. MEASUREMENTS AND MAIN RESULTS: Peak inspiratory pressure in decelerating-flow was highly correlated ( r 2 = 0.99; p < 0.001) with plateau pressure in square-flow. Peak inspiratory pressure was 1.0 ± 0.6 cm H2 O higher than plateau pressure, with 96% of values within 2 cm H2 O. The single outlier had coexistent asthma and inspiratory flows that did not reach zero. CONCLUSIONS: Peak inspiratory pressure measured during decelerating-flow ventilation may be an adequate surrogate of plateau pressure in pediatric acute respiratory distress syndrome when inspiratory flow approaches zero. Practitioners should be aware that peak inspiratory pressures in decelerating-flow may not be substantially higher than plateau pressures.